2019
DOI: 10.3847/2041-8213/ab0f40
|View full text |Cite
|
Sign up to set email alerts
|

The Sporadic Activity of (6478) Gault: A YORP-driven Event?

Abstract: On 2019 January 5 a streamer associated with the 4-10 km main-belt asteroid (6478) Gault was detected by the ATLAS sky survey, a rare discovery of activity around a main-belt asteroid. Archival data from ATLAS and Pan-STARRS1 show the trail in early December 2018, but not between 2010 and January 2018. The feature has significantly changed over one month, perfectly matching predictions of pure dust dynamical evolution and changes in observing geometry for a short release of dust around 2018 October 28. Follow-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
60
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 29 publications
15
60
4
1
Order By: Relevance
“…with large macroporosity. As a main conclusion, our analysis definitely rules out the spin-barrier classical value of about 2 hours, as claimed by Kleyna et al (2019).…”
Section: Rotation and Spin-barrier Critical Periodsupporting
confidence: 83%
See 1 more Smart Citation
“…with large macroporosity. As a main conclusion, our analysis definitely rules out the spin-barrier classical value of about 2 hours, as claimed by Kleyna et al (2019).…”
Section: Rotation and Spin-barrier Critical Periodsupporting
confidence: 83%
“…No firm estimate of Gault's rotation period was available until cometary activity was first discovered on 2019 Jan 5 (Smith & Denneau 2019). Subsequent photometric follow up to obtain an accurate lightcurve of the object did not lead to any conclusive result, likely due to the masking effect of dust in the coma (Kleyna et al 2019;Ye, et al 2019;Man-To et al 2019;Jewitt et al 2019;Sanchez et al 2019). Based on a Lomb-Scargle and ANOVA lightcurve analysis, Kleyna et al (2019) recently proposed for Gault a rotation period about 2 hours, which implied a density of about 2.7 g cm −3 as for a typical S-type asteroid.…”
Section: Introductionmentioning
confidence: 98%
“…(d∼100 µm) derived from morphological analysis of the tails (Jewitt et al 2019;Kleyna et al 2019;Moreno et al 2019;Ye et al 2019b), implying that they do not contain a preponderance of Rayleigh scatterers.…”
Section: Possible Origins For Spectral Variabilitymentioning
confidence: 99%
“…The index is typically q ∼ 3.5 (Jewitt et al 2016, Ishiguro et al 2016a, Kim et al 2017, Moreno et al 2012) although smaller (e.g. q = 1.7, Kleyna et al 2019) and larger indices (e.g. q = 3.8, Ishiguro et al 2016b) have been reported.…”
Section: Observationsmentioning
confidence: 99%